Quality of Service and Customer Satisfaction in Educational Institutions. The case of INTERPASS S.A.C. in 2021 - Sánchez Silva, Marlo Jamilton (2023)
The aim of this article was to investigate the relationship between service quality and customer satisfaction in the educational services provided by INTERPASS S.A.C. in Lima in 2021. The study used a survey technique and a questionnaire as data collection tool, with a sample of 325 students selected through random sampling. To test the hypothesis, the study employed Chi-square statistics and Spearman's correlation test. The results showed a statistically significant association between service quality and customer satisfaction. The statistical analysis confirmed the study’s main hypothesis that there is a positive impact of service quality on customer satisfaction in the company studied. This was evidenced by a high Chi-square value of 374.952 and a strong Spearman correlation of 0.806, indicating a significant relationship between the two variables.